The Differential Impact of Multimorbidity Patterns and Subsequent Accumulation on Longitudinal Trajectories of Physical Function Decline in a Population-Based Cohort of Older People. Issue 8 (24th December 2021) - Liu, Huiying; Zhang, Xinyan; Chen, Beizhuo; Fang, Boye; Lou, Vivian W Q; Hu, Jian
Abstract: Background: Although both the patterns and accumulation of multimorbidity are important for predicting physical function, studies have not simultaneously examined their impact on functional decline. This study aimed to associate multimorbidity patterns and subsequently developed conditions with longitudinal trajectories of functional decline, and it tested whether the effects of newly developed conditions on functional decline varied across distinct multimorbidity patterns. Methods: We included 6 634 participants aged at least 60 years from the China Health and Retirement Longitudinal Survey. Latent class analysis identified multimorbidity patterns from 14 chronic conditions. Mixed negative binomial models estimated the changes in physical function measured across 4 waves as a function of multimorbidity patterns, subsequently developed conditions, and their interactions. Results: Five distinct patterns were identified 3 years before Wave 1: stomach/arthritis (15.7%), cardiometabolic (6.7%), arthritis/hypertension (47.9%), hepatorenal/multisystem (18.3%), and lung/asthma (11.4%). The hepatorenal/multisystem and the lung/asthma pattern were associated with worse baseline physical function, and the hypertension/arthritis pattern was associated with greater decline of physical function. The effect of developing new conditions on decline of physical function over time was most evident for individuals from the cardiometabolic pattern. Conclusions: Considering both the combinations and progressive nature of multimorbidity is important for identifying individuals at greater risk of disability. Future studies are warranted to differentiate the factors responsible for the progression of chronic conditions in distinct multimorbidity patterns and investigate the potential implications for improved prediction of functional decline.